Oblique Gravity Wave Propagation During Sudden Stratospheric Warmings. Issue 1 (10th January 2020) - Stephan, C. C.; Schmidt, H.; Zülicke, C.; Matthias, V.
Abstract: Gravity waves (GWs) are important for coupling the mesosphere to the lower atmosphere during sudden stratospheric warmings (SSWs). Here, a minor SSW is internally generated in a simulation with the upper‐atmosphere configuration of the ICOsahedral Nonhydrostatic model. At a horizontal resolution of 20 km the simulation uses no GW drag parameterizations but resolves large fractions of the GW spectrum explicitly, including orographic and nonorographic sources. Consistent with previous studies, the simulated zonal‐mean stratospheric warming is accompanied by zonal‐mean mesospheric cooling. During the course of the SSW the mesospheric GW momentum flux (GWMF) turns from mainly westward to mainly eastward. Waves of large phase speed (40–80 m s − 1 ) dominate the eastward GWMF during the peak phase of the warming. The GWMF is strongest along the polar night jet axis. Parameterizations of GWs usually assume straight upward propagation, but this assumption is often not satisfied. In the case studied here, a substantial amount of the GWMF is significantly displaced horizontally between the source region and the dissipation region, implying that the local impact of GWs on the mesosphere does not need to be above their local transmission through the stratosphere. The simulation produces significant vertically misaligned anomalies between the stratosphere and mesosphere. Observations by the Microwave Limb Sounder confirm the poleward tilt with height of the polar night jet and horizontal displacements between mesospheric cooling and stratospheric warming patterns. Thus, lateral GW propagation may be required to explain the middle‐atmosphere temperature evolution in SSW events with significant zonally asymmetric anomalies. Key Points: A sudden stratospheric warming occurs in a high‐resolution simulation with resolved gravity waves Oblique propagation accounts locally for up to 60% of mesospheric gravity wave momentum flux The simulation produces zonal shifts between stratospheric and mesospheric temperature anomalies